2023
DOI: 10.1186/s13023-023-02617-5
|View full text |Cite
|
Sign up to set email alerts
|

Brain malformations in diprosopia observed in clinical cases, museum specimens and artistic representations

Abstract: Background Diprosopus is a rare malformation of still unclear aetiology. It describes a laterally double faced monocephalic and single-trunk individual and has to be distinguished from the variant Janus type diprosopus. Results We examined seven double-faced foetuses, five showing true diprosopus, and one each presenting as monocephalic Janiceps and parasitic conjoined twins. Four of the foetuses presented with (cranio)rachischisis, and two had se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Laterally united conjoined twins share vast parts of their body (abdomen, thorax, neck, face and/or head) and classically consists of two phenotypes: parapagus dicephalus (two heads) and parapagus diprosopus (two laterally oriented faces in a single compound head). One of the more striking and relatively often occurring discordances found in dicephalic twins is anencephaly, with at least seven described cases appearing in the recent literature [9,14,15,[25][26][27][28]56]. These unilaterally occurring neural tube defects should be distinguished from concordant neural tube defects in parapagus diprosopus, which are the consequence of interaction aplasia, a phenomenon comprehensively described elsewhere [3].…”
Section: Discordance In Laterally United Twinsmentioning
confidence: 99%
“…Laterally united conjoined twins share vast parts of their body (abdomen, thorax, neck, face and/or head) and classically consists of two phenotypes: parapagus dicephalus (two heads) and parapagus diprosopus (two laterally oriented faces in a single compound head). One of the more striking and relatively often occurring discordances found in dicephalic twins is anencephaly, with at least seven described cases appearing in the recent literature [9,14,15,[25][26][27][28]56]. These unilaterally occurring neural tube defects should be distinguished from concordant neural tube defects in parapagus diprosopus, which are the consequence of interaction aplasia, a phenomenon comprehensively described elsewhere [3].…”
Section: Discordance In Laterally United Twinsmentioning
confidence: 99%
“…Various authors suggested that duplication of the pituitary gland could be the least severe form of this anomaly [ 3 , 4 ]. Craniofacial duplication can happen together with a broad variety of anomalies, in particular those affecting the central nervous system, among which anencephaly is the most severe malformation described in diprosopus [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Craniofacial duplication can happen together with a broad variety of anomalies, in particular those affecting the central nervous system, among which anencephaly is the most severe malformation described in diprosopus [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%